A study protocol of a randomised controlled trial to measure the effects of an augmented prescribed exercise programme (APEP) for frail older medical patients in the acute setting. Issue 1 (December 2016) - McCullagh, Ruth; O'Connell, Eimear; O'Meara, Sarah; Perry, Ivan; Fitzgerald, Anthony; O'Connor, Kieran; Horgan, N.; Timmons, Suzanne
Abstract Background Older adults experience functional decline in hospital leading to increased healthcare burden and morbidity. The benefits of augmented exercise in hospital remain uncertain. The aim of this trial is to measure the short and longer-term effects of augmented exercise for older medical in-patients on their physical performance, quality of life and health care utilisation. Design & Methods Two hundred and twenty older medical patients will be blindly randomly allocated to the intervention or sham groups. Both groups will receive usual care (including routine physiotherapy care) augmented by two daily exercise sessions. The sham group will receive stretching and relaxation exercises while the intervention group will receive tailored strengthening and balance exercises. Differences between groups will be measured at baseline, discharge, and three months. The primary outcome measure will be length of stay. The secondary outcome measures will be healthcare utilisation, activity (accelerometry), physical performance (Short Physical Performance Battery), falls history in hospital and quality of life (EQ-5D-5 L). Discussion This simple intervention has the potential to transform the outcomes of the older patient in the acute setting. Trial registration ClinicalTrials.gov Identifier:NCT02463864, registered 26.05.2015.